2007
DOI: 10.1039/b705320g
|View full text |Cite
|
Sign up to set email alerts
|

Gold-catalyzed cyclizations of alkyne propargylic acetates to 2,3-bis(alkylidene)cycloalkanones and their related benzene derivatives

Abstract: We report a new and highly-convenient Au-catalyzed cyclization of alkyne propargylic acetates leading to 2,3-bis(alkylidene)cyclohexanones and their cycloadditions with a pendant dienophile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Toste et al reported silver-catalyzed 1,3-acyl migration of a nonterminal propargylic esters (Type A) to the highly functionalized aromatic compounds (Type A1). 12 During our study, the standard conditions towards alkynes-propargylic acetates like D did not afford the expected diene products, but exhibited a different mode of reactions to give the [n,2,0]bicyclic products like D2. 6 Next, Liu group has reported about a goldcatalyzed allene formation via 1,3-acyl migration of a propargyl carbonates (Type A1).…”
Section: Introductionmentioning
confidence: 65%
“…Toste et al reported silver-catalyzed 1,3-acyl migration of a nonterminal propargylic esters (Type A) to the highly functionalized aromatic compounds (Type A1). 12 During our study, the standard conditions towards alkynes-propargylic acetates like D did not afford the expected diene products, but exhibited a different mode of reactions to give the [n,2,0]bicyclic products like D2. 6 Next, Liu group has reported about a goldcatalyzed allene formation via 1,3-acyl migration of a propargyl carbonates (Type A1).…”
Section: Introductionmentioning
confidence: 65%
“…(12.18)) [62]. Oh has reported the gold(I)-catalyzed rearrangement/cyclization of alkynyl propargyl acetates to form naphthyl ketone derivatives [63] and 2,3-bis(alkylidiene)cycloalkanones [64]. As an example of the former transformation, treatment of propargylic acetate 42 with a catalytic mixture of sodium tetrachloroaurate and triphenylphosphine in DCE at room temperature for 30 min led to isolation of naphthyl ketone 43 in 90% yield (Eq.…”
Section: Acyl Migration Followed By Nucleophilc Attackmentioning
confidence: 99%
“…In a similar vein, cyclizations of diynes bearing propargyl carboxylates have been described to synthesize dienes 232 and pyrones (equation 90). 233 In the last case, a new cascade allows the intermolecular addition of electron-rich arenes.…”
mentioning
confidence: 97%